Animal Welfare Ethics in Research and Testing: Implementation and its Barrier - Sutiastuti Wahyuwardani; S M Noor; B Bakrie (Indonesian Center for Animal Research and Development, 2020)
Animals have an important role in research and testing to improve human and animal health. Animal usage must be balanced between science and ethical values of animal welfare. This paper discusses the role of IACUC, the implications of animal welfare for research, animal ethical clearance and obstacles in the implementation of animal welfare. Institution of Animal Care Use Committee (IACUC) has an important role to ensure that researcher has animal ethical clearance before conducting research and testing. Research and testing using animal should comply with ethical principles: respect, beneficiary and justice; 3Rs principles: Replacement, Reduction, Refinement and 5F/Freedom: freedom from hunger and thirst, heat and discomfort, pain, trauma and disease, fear and stress and expressing behavior naturally. The application of animal ethics clearance in Indonesia in research using animals is compulsary in various institutions, However thera are several barriers in its implementation, Those are: not all research institutions have IACUC, lack of awareness of researchers to apply for animal ethical clearance, reluctant to IACUC requirements, lack of facilities animals that meet animal welfare requirements and lack of competence in animal handling according to animal welfare.